EuroFIR Project – A Key Role in Creation and Compiling of Bulgarian Food Composition Database - Gyurova, Desislava Krasteva (International Journal of Medical and Health Sciences Research, 2014)
The food chemical composition databases provide a detailed information on nutritional composition, derived from the specific needs of each country. Data sources and their quality should be documented for each nutrient and in accordance with international and regional standards. The collaboration with leadership of the EuroFIR Project and contacts with various representatives of the participating countries contributed to capacity development in our country in a following way: EuroFIR workshops, training courses, self training.Thus, only helped the professional growth of staff to learn the basic criteria for correct description, identification of foods and establishment and compiling of Bulgarian food chemical composition database. Bulgarian Food Composition Data Base includes 828 foods with 37 nutrients for each food: • English food names and Bulgarian food names • No Scientific names • 828 food codes • Original Food Group • Nitrogen to protein conversion factor (NCF) and the Fatty acid conversion factor (FACF) were provided for a number of foods • LanguaL food description - for all foods